G153 Determinants of Quality of Life in Children with Asthma Who Live in Scotland. (4th June 2013) - Turner, SW; Mehta, A; Ayres, JG; Palmer, CN; Mukhopadhyay, S
Abstract : Background: Childhood asthma is a common chronic condition which may be associated with reduced quality of life (QoL). Factors which determine QoL are important to child, parent and clinician and, in particular, factors which are modifiable are of interest and may be amenable to intervention. The aim of the present study was to identify which factors are associated with reduced QoL in children with asthma. Methods: Children aged 2–16 years and with physician diagnosed asthma were recruited from primary and secondary care as part of a study designed to relate gene-environment interactions to asthma outcomes. The Paediatric Asthma Quality of Life Questionnaire was completed and related to the following plausible determinants: gender, age, socioeconomic status, primary or secondary care, BTS treatment step (index of severity), asthma control, exposure to second hand smoke, spirometry and exhaled nitric oxide. Results: There were 894 children recruited, mean age 9.5 years, 53% male, 27% recruited in primary care. QoL was determined in 565 children, median score [IQR] 5.9 [4.7, 6.8]. In univariate analyses, QoL was positively associated with increasing affluence (Rho 0.14) and better asthma control (rho 0.63) and negatively with smoking exposure (median 5.2 vs 6.0 for non-exposed), recent exacerbations (median 5.3 vs 6.2 for no exacerbation) and BTS treatment step (rho –0.32). QoL was not related to spirometry or exhaled NO. In the multivariate analysis (R2 = 0.31, n = 255), log transformed QoL was positively associated with socioeconomic status (p = 0.004) and asthma control (p < 0.001) and inversely associated with BTS treatment step (p = 0.004). Conclusions: Overall, the QoL was good for this population. This insight suggests at least three independent drivers for QoL, asthma control, asthma severity and socioeconomic status, of which asthma control is the factor most amenable to intervention. Other factors not captured in this study, such as compliance and attitude to health and disease, are likely to be important.